2009
DOI: 10.3109/02841850903213822
|View full text |Cite
|
Sign up to set email alerts
|

Progression of emphysema evaluated by MRI using hyperpolarized 3he (hp 3he) measurements in patients with alpha-1-antitrypsin (a1at) deficiency compared with CT and lung function tests

Abstract: This pilot study indicates the possible use of nonionizing HP (3)He MRI for monitoring the progression of emphysema. However, in the future, larger studies are needed to confirm these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Although the AATD patients and COPD ex-smokers were previously investigated by pioneers of diffusionweighted MRI using ADCs (44)(45)(46)(47), to our knowledge, this is the first direct comparison of morphometry modeling approaches across a wide spectrum of emphysema severity that is commonly observed in patients. This is important because both the extent and severity of emphysema differs significantly in elderly neversmokers and within patient subgroups, including those with smoking-related emphysema and patients with emphysema-related to AATD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the AATD patients and COPD ex-smokers were previously investigated by pioneers of diffusionweighted MRI using ADCs (44)(45)(46)(47), to our knowledge, this is the first direct comparison of morphometry modeling approaches across a wide spectrum of emphysema severity that is commonly observed in patients. This is important because both the extent and severity of emphysema differs significantly in elderly neversmokers and within patient subgroups, including those with smoking-related emphysema and patients with emphysema-related to AATD.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent diffusion coefficients (ADCs) and respective maps of fully inflated lungs of healthy subjects are relatively homogeneous, and this uniformity is a hallmark of the normal lung, demonstrating regional confinement by the lungs' microstructure (6)(7)(8)(9). ADC maps in patients with emphysema have been shown to be nonuniform and to contain larger diffusion values (2,5,10,11), correlating well with the onset and progression of the disease, where the degree and location of destruction varies throughout the lung (8,(12)(13)(14)(15). Similarly, the choice of variables such as gradient strength, duration, and time between pulses to induce the diffusion sensitization has been shown to induce variability in the observed ADCs (14).…”
Section: Thoracic Imaging: Effect Of Lung Inflation Level On Apparentmentioning
confidence: 99%
“…However, lacunarity, a measure of the inhomogeneity in distribution of ADC values, did correlate with disease progression (Diaz et al, 2009). In a 2-year study in ␣1-antitrypsin-deficient patients, significant changes were reported for forced expiratory volume in 1 s, diffusion of CO, tissue density, and emphysema index from CT, but the increase in 3 He ADC values just missed significance (Stavngaard et al, 2009).…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%